Drug court - Gallagher, John R. (Handbook of forensic social work, 2024)
This chapter examines the role of drug court in the criminal justice system, describes how social work values are consistent with the drug court model, and provides up-to-date research related to the effectiveness of drug court in reducing criminal recidivism rates for individuals who have substance use disorders. It discusses best practices in serving racial, ethnic, sexual, and gender minorities in drug court, explores common ethical dilemmas social workers may face when working in drug court, and provides a case study that includes an example treatment plan, substance use disorder and mental health diagnostic impressions, and a description of evidence-based interventions that social workers can use in drug court to promote substance use disorder and mental health recovery.